Development of a Real-Time Quantitative RT-PCR Assay for Detection of Bovine Rhinitis B Virus - Xie, Yi-Lun; Lv, Dian-Hong; Wen, Xiao-Hui; Zhai, Qi; Luo, Man-Lin; Wei, Wen-Kang; Chen, Qin-Ling; Zhai, Shao-Lun (Frontiers in Veterinary Science, 2021)
Bovine rhinitis B virus (BRBV) has been frequently identified in cattle diagnosed with bovine respiratory disease complex (BRDC) in recent years, suggesting potential contribution to BRDC. To provide an efficient tool to detect BRBV, the goal of this study was to develop a TaqMan-based real-time RT-PCR assay for BRBV detection. A pair of primers and a probe were designed based on the 3D gene of the BRBV genome. The assay was specific for BRBV and able to exclude bovine rhinitis A virus, foot-and-mouth disease virus and Senecavirus A. The limit of detection of the assay was 4.46 copies per reaction. A standard curve was plotted, with a coefficient of determination of 0.999 between the concentration of 10-3 - 108 copies/µL. The reproducibility of the assay was acceptable, with the standard deviation lower than 1.00 in both intra- and inter-assay. Of 200 samples collected from 150 heads of cattle in recent years in China, 11% (22/200) of the samples tested positive in the assay, i.e., 4.6% (7/150) of the cattle were BRBV positive. This study provided an efficient diagnostic tool for the epidemiological investigations of BRBV.